Integration of Analytical Chemistry Flipbooks Based on Project-Based Learning in Improving Critical Thinking Skills and Scientific Literacy to Support SDG-4 - Sari, Sri Adelila; Dewi, Ratna Sari; Kembaren, Agus; Hasibuan, Hanisah; Talib, Corrienna Abdul; Saputra, Kana (Jurnal Pendidikan IPA Indonesia, 2025)
This study was aimed at assessing the effectiveness of Project-Based Learning (PjBL)-based analytical chemistry flipbooks in improving students’ critical thinking skills and scientific literacy, and linking the results to the achievement of Sustainable Development Goals (SDG-4), namely quality education. This study used a quantitative approach with a quasi-experimental design, involving two groups: an experimental group (n = 250) using PjBL-based flipbooks, and a control group (n = 250) using conventional textbooks. The projects in PjBL were designed to challenge students to apply critical thinking skills in solving real problems in analytical chemistry. Scientific literacy was measured based on students’ ability to understand, evaluate, and apply chemical concepts in the context of the project. Critical thinking skills and scientific literacy tests were used to measure learning outcomes before and after the intervention. The instrument in this study was a test of critical thinking skills and scientific literacy. Statistical tests showed that the data were normally distributed (significance value 0.216), homogeneous variance (0.074), and significant differences between the experimental and control groups (t = 0.038, p < 0.05). The increase in n-gain in the experimental group reached 0.9 (high category), compared to 0.63 (moderate category) in the control group. This study concluded that Project-Based Learning-based flipbooks were significantly more effective than conventional textbooks in improving students’ critical thinking skills and scientific literacy. The results of this study confirmed the superiority of PjBL-based flipbooks in significantly improving students’ critical thinking skills and scientific literacy compared to conventional textbooks. Statistical data support (normal distribution, homogeneous variance, significant differences between groups, and high n-gain in the experimental group) encourages the adoption of PjBL-based flipbooks as an effective learning strategy to achieve quality education according to SDG-4.